3D equilibrium reconstruction with islands *Notice of Copyright. This manuscript has been authored by UT-Battelle, LLC under Contract No. DE-AC05-00OR22725 with the U.S. Department of Energy. The United States Government retains and the publisher, by accepting the article for publication, acknowledges that the United States Government retains a non-exclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. The Department of Energy will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (6th March 2018) - Cianciosa, M; Hirshman, S P; Seal, S K; Shafer, M W
Abstract: This paper presents the development of a 3D equilibrium reconstruction tool and the results of the first-ever reconstruction of an island equilibrium. The SIESTA non-nested equilibrium solver has been coupled to the V3FIT 3D equilibrium reconstruction code. Computed from a coupled VMEC and SIESTA model, synthetic signals are matched to measured signals by finding an optimal set of equilibrium parameters. By using the normalized pressure in place of normalized flux, non-equilibrium quantities needed by diagnostic signals can be efficiently mapped to the equilibrium. The effectiveness of this tool is demonstrated by reconstructing an island equilibrium of a DIII-D inner wall limited L-mode case with an n = 1 error field applied. Flat spots in Thomson and ECE temperature diagnostics show the reconstructed islands have the correct size and phase.